Assessment of lipid composition and eicosapentaenoic acid/docosahexaenoic acid bioavailability in fish oil obtained through different enrichment methods - Song, Rongzhen; Li, Wen; Deng, Shanggui; Zhao, Yueliang; Tao, Ningping (Frontiers in Nutrition, 2023)
Abstract In this study, we analyzed the eicosapentaenoic acid/docosahexaenoic acid (EPA/DHA) lipid composition of fish oil obtained through enzymatic treatment, fractional distillation and silica gel column purification. We further assessed EPA/DHA bioavailability in a Caco-2 cell monolayer model. Results showed that enzymatic treatment improved the incorporation of EPA/DHA as diacylglycerol (DG) while silica gel column chromatography enriched the content of EPA/DHA as phosphatidylglycerol (PG) (12.58%) and phosphatidylethanolamine (PE) (4.99%). Furthermore, increasing the purity of EPA/DHA could improve its bioavailability and after 24 incubation, binding forms of triglyceride (TG) was superior to ethyl ester (EE) (p＜0.05) at the same purity level.